The USE OF REVERSED CLASSROOM LEARNING MODEL TO IMPROVE STUDENTS’ SKILLS IN WRITING DESCRIPTION TEXT - Sofiyah; Mira Nuryanti; Muliawati, Hesti (Cirebon International Conference on Education and Economics Proceeding, 2024)
In this modern era with the sophistication of digital technology, teachers are required to be able to understand and have skills in using learning models. So that learning is easily understood by students. So, the learning used must be effective and efficient. To fulfill all that, researchers use the inverted classroom learning model in learning to write description text. The purpose of this study is to determine students' activities using the flipped classroom learning model in learning to write description text and to determine the effectiveness of the flipped classroom learning model. This research consists of three stages. Each stage consists of an initial test before treatment and a final test after treatment. The information collection strategies utilized were perception, survey, and test come about. The investigate strategy utilized was a pseudo-experimental strategy with a time arrangement plan. The research shows that the learning of descriptive text using the flipped classroom learning model is more effective. This can be seen from the average value at each stage of the test, the final test conducted is higher and significant than the initial test. Based on the results of the research that has been conducted by researchers at SMP Negeri 1 Susukan, Cirebon Regency by using the inverted classroom learning model in learning description text is effectively used to improve students' ability to write description text.